Evidence for a DNA-Based Mechanism of Intron-Mediated Enhancement - Rose, Alan B.; Emami, Shahram; Bradnam, Keith; Korf, Ian (Frontiers in Plant Science, 2011)
Many introns significantly increase gene expression through a process termed Intron-Mediated Enhancement (IME). Introns exist in the transcribed DNA and the nascent RNA, and could affect expression from either location. To determine which is more relevant to IME, hybrid introns were constructed that contain sequences from stimulating Arabidopsis thaliana introns either in their normal orientation or as the reverse complement. Both ends of each intron are from the non-stimulatory COR15a intron in their normal orientation to allow splicing. The inversions create major alterations to the sequence of the transcribed RNA with relatively minor changes to the DNA structure. Introns containing portions of either the UBQ10 or ATPK1 intron increased expression to a similar degree regardless of orientation. Also, computational predictions of IME improve when both intron strands are considered. These findings are more consistent with models of IME that act at the level of DNA rather than RNA.